ChemInform Abstract: Chemoenzymatic Synthesis of 3′‐Deoxy‐3′‐(4‐substituted‐triazol‐1‐yl)‐5‐methyluridine. Issue 20 (20th May 2014) - Arya, Anu; Mathur, Divya; Tyagi, Abhilash; Kumar, Rajesh; Kumar, Vinod; Olsen, Carl E.; Saxena, Rajendra K.; Prasad, Ashok K.
Abstract A series of triazoles (III) (9 examples) is readily synthesized by a Huisgen 1, 3‐dipolar cycloaddition reaction of alkynes (II) with azide (I), which is chemoenzymatically prepared starting from D‐xylose.